Preclinical development of a molecular clamp‐stabilised subunit vaccine for severe acute respiratory syndrome coronavirus 2. Issue 4 (5th April 2021) - Watterson, Daniel; Wijesundara, Danushka K; Modhiran, Naphak; Mordant, Francesca L; Li, Zheyi; Avumegah, Michael S; McMillan, Christopher LD; Lackenby, Julia; Guilfoyle, Kate; van Amerongen, Geert; Stittelaar, Koert; Cheung, Stacey TM; et al.
Abstract: Objectives: Efforts to develop and deploy effective vaccines against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) continue at pace. Here, we describe rational antigen design through to manufacturability and vaccine efficacy of a prefusion‐stabilised spike (S) protein, Sclamp, in combination with the licensed adjuvant MF59 'MF59C.1' (Seqirus, Parkville, Australia). Methods: A panel recombinant Sclamp proteins were produced in Chinese hamster ovary and screened in vitro to select a lead vaccine candidate. The structure of this antigen was determined by cryo‐electron microscopy and assessed in mouse immunogenicity studies, hamster challenge studies and safety and toxicology studies in rat. Results: In mice, the Sclamp vaccine elicits high levels of neutralising antibodies, as well as broadly reactive and polyfunctional S‐specific CD4 + and cytotoxic CD8 + T cells in vivo . In the Syrian hamster challenge model ( n  = 70), vaccination results in reduced viral load within the lung, protection from pulmonary disease and decreased viral shedding in daily throat swabs which correlated strongly with the neutralising antibody level. Conclusion: The SARS‐CoV‐2 Sclamp vaccine candidate is compatible with large‐scale commercial manufacture, stable at 2–8°C. When formulated with MF59 adjuvant, it elicits neutralising antibodies and T‐cell responses and provides protection in animal challenge models. Abstract : We describe preclinical development of a prefusion stabilized spike protein subunit vaccine for SARS‐CoV‐2. Results include structural resolution by cryo‐electron microscopy, mouse immunogenicity and a hamster protection study.